The distribution and characteristics of bacteria in recreational river water of a community resort in Baram, Sarawak, Malaysian Borneo - Lihan, S.; Tian, P.K; Chiew, T.S; Ching, C.L; Shahbudin, A; Hussain, H.; Mohd-Azlan., J (Universiti Putra Malaysia, 2016)
Enterobacteriaceae is a large family within the Gram-negative bacteria that primarily inhabits in the gastrointestinal tract of human and animals. The bacteria within this group are readily survived in the environment with some species found living free in the water where energy sources are scarce, making them ideal indicators for faecal contamination of the river water. Some species within the family have been used as indicator for the presence of pathogenic bacteria whilst on the other hand some species have been directly associated with various diseases in human and animals. The main aim of this research study was to determine the distribution and characteristics of the Enterobacteriaceae in water samples collected from river and waterfalls within a community resort. The health risk associated with the bacteria was analysed with regard to their susceptibility to antibiotics. Samples were collected from surface water and water falling down directly from waterfalls of river within the community resort. The samples collected were plated onto Eosine Methylene Blue agar (EMBA) for the isolation of the Enterobacteriaceae. Bacterial colonies growing on the agar were randomly picked, purified, stocked and then identified using API 20E identification kit. DNA fingerprinting using (GTG)5-PCR was utilised to determine their genetic profiles before the isolates were grouped into a dendrogram using RAPDistance software package. The level of antibiotic susceptibility of the bacteria isolates was analysed using disc diffusion technique. This study confirmed the presence of Enterobacter, Klebsiella, Citrobacter, Pantoea and Serratia in the water samples with their single and multiple antibiotic resistance and susceptible characteristics. The dendrogram presented in this study shows genetic similarities and differences among the strains, suggesting while there is a potential for single distribution of a clone, there is also possibility of the distribution of different strains within species in the water environment. Therefore, awareness on the potential risk associated with genetically diverse intermediate and resistant enteric bacteria in the recreational water should be communicated to the public especially communities within the study area.